2020
DOI: 10.3390/mi11090813
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Flow in Micro Electrokinetic Turbulent Mixer

Abstract: In the present work, we studied the three-dimensional (3D) mean flow field in a micro electrokinetic (μEK) turbulence based micromixer by micro particle imaging velocimetry (μPIV) with stereoscopic method. A large-scale solenoid-type 3D mean flow field has been observed. The extraordinarily fast mixing process of the μEK turbulent mixer can be primarily attributed to two steps. First, under the strong velocity fluctuations generated by μEK mechanism, the two fluids with different conductivity are highly mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…They hypothesized that there existed a largescale secondary flow caused by the imbalance of AC electroosmotic flow (ACEOF) near the top and bottom walls. Then, Nan et al 50 observed the 3D flow field using microparticle image velocimetry (μPIV) and verified the existence of a large-scale swirling flow that can enhance entrainment in the μEK turbulent micromixer.…”
mentioning
confidence: 99%
“…They hypothesized that there existed a largescale secondary flow caused by the imbalance of AC electroosmotic flow (ACEOF) near the top and bottom walls. Then, Nan et al 50 observed the 3D flow field using microparticle image velocimetry (μPIV) and verified the existence of a large-scale swirling flow that can enhance entrainment in the μEK turbulent micromixer.…”
mentioning
confidence: 99%
“…Therefore, the mixing of fluids can be enhanced by nonlinear EK flow induced near electrodes. Besides, due to the unbalanced electric field on the low and high electric conductivity streams, a large scale vortical flow can be generated by the electro-osmotic flow (EOF) adjacent to the top and bottom walls, as have been investigated by Nan et al [25]. The vortical flow could significantly enhance the 3D mixing of fluids on large scales.…”
Section: Electric Field Effectmentioning
confidence: 99%
“…Recently, many works on electrokinetic instability (EKI) were accomplished and attracted much attention, it is a phenomenon described by charge accumulation at perturbed interfaces due to electrical conductivity gradients, which exist in the bulk flow [16][17][18][19][20]. Although many significant results have already been obtained through those previous works [21][22][23][24][25], much effort is still needed to improve our understanding of electrokinetic mixing under AC electric field, to make the electrokinetic micromixers more efficient and flexible for "lab-on-a-chip" applications.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most explored approaches for trying to achieve turbulent flow characteristics in microchannels is the use of electrokinetic forcing [9,10]. For example, as argued by the authors, Wang et al [11] have reported a direct observation of the existence of "turbulence" in microfluidics with Re ∼ 1 in a pressure-driven flow under electrokinetic forcing using a novel velocimeter with ultrahigh spatiotemporal resolution.…”
Section: Nomenclaturementioning
confidence: 99%